Implementation of The Principle of Equality before The Law on The Fulfillment of The Rights of Persons with Disabilities in Obtaining Legal Services at The Religious Court of Surakarta City - Mahendra Akbar Rachmadhani; Syaifuddin Zuhdi (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the implementation of the principle of equality before the law in terms of the rights of persons with disabilities to obtain legal services at the Surakarta City Religious Court. This study used interviews with judges, lawyers, court officers, and people with disabilities, as well as direct observation of existing facilities and accessibility in the court. This research method is based on an empirical juridical method. In addition, this study analyzes whether the principle of equality before the law is applied effectively, by looking at the example of Law Number 8 of 2016 concerning Persons with Disabilities. The results of the study show that, although there have been efforts to fulfill the rights of persons with disabilities in the judiciary, there are still some challenges to applying the principle of equality before the law. Among them are the lack of disability-friendly court facilities and the lack of adequate communication assistance. and the inability of court officers to understand the rights of persons with disabilities. People with disabilities often have difficulty accessing courtrooms, getting proper information about the law, and getting proper legal assistance. Therefore, while there are regulations that support the rights of persons with disabilities in the justice system, practice on the ground still needs to make further efforts to ensure that everyone has an equal opportunity to access legal services and access. The study suggests improving physical court facilities, improving legal support services, and specialized training for law enforcement to increase understanding and awareness of the rights of persons with disabilities in the judicial process.